(untitled) (Acta Scientiarum. Health Sciences, 2020)
To describe the family’s experience in home care for children and adolescents with special health needs. Qualitative research supported by the theoretical framework of Patient- and Family-Centered Care, carried out in an Association that serves Children and Adolescents who need special health care in a municipality in the southern region of Brazil. Data were collected through semi-structured interviews with eight mothers of children and adolescents with special health care needs, which were recorded and transcribed verbatim, and subjected to content analysis in the thematic modality. Two categories were identified: Family reorganization to care for children with special health care needs at home; and Invisibility of the woman/mother. Caring for CSHCN at home imposes on families the need to reorganize themselves, so that the mother can dedicate herself, almost entirely, to this function, including neglecting health care. Despite this dedication, mothers do not recognize activities developed as difficult; however they make self-care invisible in relation to child care.